2019
DOI: 10.3389/fpsyg.2019.01716
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Optimal Autonomic State for Enhanced Flow and Executive Task Performance?

Abstract: Introduction Flow describes a state of optimal experience that can promote a positive adaptation to increasing stress. The aim of the current study is to identify the ideal autonomic state for peak cognitive performance by correlating sympathovagal balance during cognitive stress with (1) perceived flow immersion and (2) executive task performance. Materials and Methods Autonomic states were varied in healthy male participants ( n = 48) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…We found that TRR amplitude was modulated by reaction time on a trial-to-trial basis. It is well known that arousal influences reaction times, with a classic inverted-U relation (25), an effect that shows up in standard physiological measures of arousal, including pupil size (10) and cardiac activity (26). So if TRR amplitude reflects arousal, as we hypothesized, we would expect that it would be higher when an observer responds faster, which is what we found (on correct trials).…”
Section: Discussionsupporting
confidence: 75%
“…We found that TRR amplitude was modulated by reaction time on a trial-to-trial basis. It is well known that arousal influences reaction times, with a classic inverted-U relation (25), an effect that shows up in standard physiological measures of arousal, including pupil size (10) and cardiac activity (26). So if TRR amplitude reflects arousal, as we hypothesized, we would expect that it would be higher when an observer responds faster, which is what we found (on correct trials).…”
Section: Discussionsupporting
confidence: 75%
“…In our experiment, this performance-enhancing effect of painful temperatures was overshadowed by an opposite negative effect of temperature on performance mediated through subjective pain ratings, but it is possible that the positive effect may predominate in certain circumstances or in certain individuals. We speculate that these direct cognition-enhancing effects of painful temperatures may be mediated through general effects of pain on sympathetic arousal 30 , which has been shown to induce an optimal state for enhanced flow and performance on executive tasks 31 . In other words, pain is always distracting, but it is also stimulating and therefore under certain circumstances it could increase the total amount of resources to be shared between task performance and pain processing.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies utilized linear regression analysis to identify associations between autonomic variables and athletic performance, despite the fact that these relations do not necessarily follow a linear relationship, as it was shown for cognitive performance 89 . In order to identify possible non-linear relationships, we have used the second-order (quadratic) regression (see: supplementary figure 1 ).…”
Section: Discussionmentioning
confidence: 99%